Kontribusi Motivasi terhadap Hasil Belajar Matematika Siswa Kelas 8 - Fadia Tasya Ardilla; RM Bambang; Dewi Annisa (Universitas Syiah Kuala, 2023)
Motivation plays a crucial role in teaching and learning activities as it significantly impacts the quality of learning outcomes, particularly in mathematics. This influence becomes evident when motivation contributes to students' learning achievements. This study aimed to examine whether motivation influenced junior high school students’ learning outcomes. A quantitative approach with a descriptive correlational design was employed. The population solely comprised Year 8 students, selected using a random sampling method. Motivational questionnaires and student learning outcome tests were utilized to collect the data. The data were analyzed using simple correlation tests. The analysis showed a relatively strong positive correlation between student motivation and mathematics learning outcomes (r=0.478). The learning motivation accounted for 22.85% of the variation in learning outcomes. Thus, it can be concluded that motivation contributes to student learning outcomes, with a relatively modest impact. The findings of this study are expected to assist teachers in emphasizing student motivation and helping students attain high levels of motivation, enabling them to solve problems with ease and achieve optimal learning outcomes.